Ocena zachowania dziecka z zaburzeniem integracji sensorycznej = Assessment of the behavior of a child with sensory integration disorder - Agnieszka Radzimińska; Katarzyna Strojek; Urszula Kaźmierczak; Magdalena Weber-Rajek; Grzegorz Srokowski; Irena Bułatowicz; Aleksander Goch; Walery Zukow (Kazimierz Wielki University, 2015)
Radzimińska Agnieszka, Strojek Katarzyna, Kaźmierczak Urszula, Weber-Rajek Magdalena,Srokowski Grzegorz, Bułatowicz Irena, Goch Aleksander, Zukow Walery. Ocena zachowania dziecka z zaburzeniem integracji sensorycznej = Assessment of the behavior of a child with sensory integration disorder. Journal of Education, Health and Sport. 2015;5(11):685-697. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.41447 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A685-697 http://pbn.nauka.gov.pl/works/686089 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015.   Ocena zachowania dziecka z zaburzeniem integracji sensorycznej Assessment of the behavior of a child with sensory integration disorder   Agnieszka Radzimińska1, Katarzyna Strojek1, Urszula Kaźmierczak1, Magdalena Weber-Rajek1,Grzegorz Srokowski1, Irena Bułatowicz1, Aleksander Goch1, Walery Zukow2   1. Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum w Bydgoszczy, Katedra Fizjoterapii, Bydgoszcz, Polska 2. Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Bydgoszcz, Polska   Adres do korespondencji: dr n. med. Agnieszka Radzimińska Uniwersytet Mikołaja Kopernika w Toruniu Collegium Medicum im. Ludwika Rydygiera w Bydgoszczy Katedra Fizjoterapii ul. Techników 3, Bydgoszcz e-mail: agnieszka.radziminska@gmail.com   Streszczenie   Metoda integracji sensorycznej (SI - Sensory Integration) jest uważana na całym świecie jako jedna z nowatorskich koncepcji pracy z dziećmi z zaburzeniami zachowania i emocji. Jest to metoda, w której wykorzystuje się różnorodne działania wspomagające rozwój dziecka. Dysfunkcje integracji sensorycznej dotyczą nieprawidłowości w zakresie przetwarzania bodźców sensorycznych w obrębie następujących systemów: czuciowego (dotykowego i proprioceptywnego), przedsionkowego, słuchowego, wzrokowego, węchowego i smakowego. W celu postawienia prawidłowej diagnozy, zaburzenia integracji sensorycznej,  należy uwzględnić dane z poszczególnych etapów badania: wywiadu z rodzicami, kwestionariuszy dotyczących funkcjonowania dziecka na co dzień, wyników prób klinicznych, wyników testów kalifornijskich. Wyniki uzyskane na podstawie w/w kwestionariuszy nie pozwalają na samodzielne stawianie diagnozy. Jest to narzędzie wstępnej diagnozy, służące do przeprowadzenia dalszej wnikliwej oceny przez terapeutę metody SI. Wiedza z zakresu integracji sensorycznej powinna być propagowana wśród szerszego grona specjalistów tj.: lekarzy, fizjoterapeutów, logopedów, neurologopedów, psychologów, a także pedagogów oraz nauczycieli.   Summary   Sensory integration method is regarded worldwide as one of the innovative concept of working with children with behavioral and emotional disorders. It is a method that uses a variety of activities supporting the development of the child. Sensory integration dysfunctions of the irregularities in the processing of sensory stimuli within the following systems: sensory (touch and proprioceptive), vestibular, auditory, visual, olfactory and flavoring. In order to make the correct diagnosis, sensory integration dysfunction, should take into account data from individual phases of the study: interview with parents, questionnaires concerning the functioning of the child on a daily basis, results of clinical trials, the test results of California. The results of these the questionnaires do not allow for self-diagnosing. It is a tool initial diagnosis, used to carry out further careful evaluation by a therapist SI method. Knowledge of sensory integration should be promoted among a wider group of experts: physiotherapists, speech therapists, psychologists and teachers.   Słowa kluczowe: zachowanie dziecka, zaburzenie integracji sensorycznej.   Key words: behavior of a child, sensory integration disorder.